Glucosinolate profiles and phylogeny in Barbarea compared to other tribe Cardamineae (Brassicaceae) and Reseda (Resedaceae), based on a library of ion trap HPLC-MS/MS data of reference desulfoglucosinolates. (May 2021) - Agerbirk, Niels; Hansen, Cecilie Cetti; Olsen, Carl Erik; Kiefer, Christiane; Hauser, Thure P.; Christensen, Stina; Jensen, Karen R.; Ørgaard, Marian; Pattison, David I.; Lange, Conny Bruun Asmussen; Cipollini, Don; Koch, Marcus A.
Abstract: A library of ion trap MS2 spectra and HPLC retention times reported here allowed distinction in plants of at least 70 known glucosinolates (GSLs) and some additional proposed GSLs. We determined GSL profiles of selected members of the tribe Cardamineae (Brassicaceae) as well as Reseda (Resedaceae) used as outgroup in evolutionary studies. We included several accessions of each species and a range of organs, and paid attention to minor peaks and GSLs not detected. In this way, we obtained GSL profiles of Barbarea australis, Barbarea grayi, Planodes virginica selected for its apparent intermediacy between Barbarea and the remaining tribe and family, and Rorippa sylvestris and Nasturtium officinale, for which the presence of acyl derivatives of GSLs was previously untested. We also screened Armoracia rusticana, with a remarkably diverse GSL profile, the emerging model species Cardamine hirsuta, for which we discovered a GSL polymorphism, and Reseda luteola and Reseda odorata . The potential for aliphatic GSL biosynthesis in Barbarea vulgaris was of interest, and we subjected P-type and G-type B. vulgaris to several induction regimes in an attempt to induce aliphatic GSL. However, aliphatic GSLs were not detected in any of the B. vulgaris types. We characterized the investigated chemotypes phylogenetically, based on nuclear rDNA internal transcribed spacer (ITS) sequences, in order to understand their relation to the species B. vulgaris in general, and found them to be representative of the species as it occurs in Europe, as far as documented in available ITS-sequence repositories. In short, we provide GSL profiles of a wide variety of tribe Cardamineae plants and conclude aliphatic GSLs to be absent or below our limit of detection in two major evolutionary lines of B. vulgaris . Concerning analytical chemistry, we conclude that availability of authentic reference compounds or reference materials is critical for reliable GSL analysis and characterize two publicly available reference materials: seeds of P. virginica and N. officinale . Graphical abstract: Image 1 Highlights: Ion-trap HPLC-MS library of retention times and MS2 data for desulfoglucosinolates. Conclusive GSL profiles of eight species from tribe Cardamineae. Conclusive, systematic lists of glucosinolates not detected in investigated species. Extensive search for aliphatic glucosinolates in Barbarea vulgaris with negative result. DNA-based (ITS) characterization of two chemotypes of B. vulgaris .